Investigation of peroxidation kinetics in oil-in-water emulsions induced by Cu(II) - Bakır, Temel kan; Arabacıoğlu, Reyhan; Kandemirli, Fatma; Şener, İzzet (Bilge International Journal of Science and Technology Research, 2018)
In this study, peroxidation of olive oil, corn oil, sunflower oil, walnut oil, argan oil, rosehip oil emulsions was carried out in the presence of copper (II) ion at 37 ° C and pH 7 in a ventilated incubation environment. Primer products (hydroperoxides) were monitored by Fe (III) SCN method and secondary products (malondialdehyde) were analyzed by TBARS analytical methods. In addition, GC-MS analysis were performed on the oils studied to identify compounds that behave as free radical scavengers or hydrogen donors. Before preparation of the oil emulsions in water, iodine index determinations of the degrees of unsaturation in the oils were made and found to be 86.28, 128.12, 140.22, 164.97, 97.29 and 183.58 gI2 / 100g for olive oil, corn oil, sunflower oil, walnut oil, argan oil and rosehip oil respectively. The rate constants were calculated kwalnut oil > kargan oil > krosehip oil > ksunflower oil > kcorn oil > kolive oil  for FeSCN method and krosehip oil > kwalnut oil > kargan oil > kolive oil > ksunflower oil > kcorn oil for TBARS method, respectively. As a result, pseudo first order kinetics of hydroperoxides and aldehydes were observed in copper-catalyzed oil emulsions at 37 ° C and pH 7, and the absorbance values obtained as a function of the incubation period gave sigmoidal curves. This study showed that the oxidation rates of fats are closely related to the conjugated fatty acids. It was thought that the kinetic data obtained could be used to accurately calculate the shelf life of oils used as food components.
Keywords: TBARS Method; Ferric Thiocyanate Method; Olive oil; Corn oil; Sunflower oil; Walnut oil; Argan oil; Food Engineering; Gıda Mühendisliği; 6. Clean water